Politics and the Plowshare: PL 480 in Crisis, 1972-80 - Caswell, Crayton (Kansas State University. Dept. of History, 2013)
Senator Robert Dole (R-Kansas) stumped for the continued support of the Agricultural Trade and Development Act, also known as PL 480 or the Food for Peace program. Since its inception in 1954, the program had had plenty of bipartisan support due to its humanitarian implications. However, in 1972 the Food for Peace program came under attack at precisely the same time that food prices skyrocketed around the globe. The marginalization of the Food for Peace program has been discussed for the period between 1972 and 1974, however the period beyond 1976 has received less attention. Through the use of government documents and the secondary scholarship, the period of 1976-1980 has brought to light the adaptive features of the Food for Peace program that enabled it to survive. The perceived purposes of the Food for Peace program at any given time dictated its funding and support. So in the early years of its existence, the point was to alleviate the effects of domestic overproduction while serving Cold War foreign policy interests at the same time. Because of this, the humanitarian aspects of the program were able to shift the program’s image by the early 1970s. This paper finds that during the more elusive period between 1976 and 1980, the Food for Peace program proved its ability to survive politically by adapting to changing political situations within the U.S. In response to increased U.S. grain sales to the Soviet Union, the program’s Cold War-inspired foreign policy objectives seemed to fade away. During this time, domestic realities dictated the use or non-use of the program to the point where its continued existence came into serious question. By 1980, its survival depended upon the shift towards a seemingly high-minded humanitarianism as well as the political reality that a global image of empathy would greatly benefit U.S. interests abroad.
Keywords: Food for Peace; PL 480; Cold War; Foreign policy; Agriculture; Agricultural Trade and Development Act